Des réductions en art aux traductions incidentes : le décentrement d’un design tactique - Grégory Marion (Appareil)
Instructed by the work of Michel de Certeau on the capacity of “ordinary culture” to affect the order of industrial production (cf. the author’s work on the art of making, “ways of practice” and the daily practices in L’Invention du quotidien—The Practice of Everyday Life, 1980), this article proposes to confront in a specific way—referring to the field of the arts, techniques and design—texts, objects or practices, in order to clear lines of discernment and to create openings. Starting from the certalian attention to “tactical procedures”, supporting translations in design, it’s about to put into discussion the paradigm of “réduction in art”, that is to say the hold of doctrines that confiscate “arts of practice” rephrasing them into discourses. Such a critical reversal, highlighting the multiple uses that translate everyday consumer products into turns and phrases, does not fail to question the designer’s task.